DEVELOPMENT OF A NEW BIVOLTINE BREED OF SILKWORM BOMBYX MORI YX MORI MU51 WITH SHORT LARVAL DURATION - ROHITH LINGAPPA SHANKAR,; G. SUBRAMANYA, (The Bioscan, 2010)
An exotic bivoltine race of silkworm Bombyx mori namely C108, and an exotic multivoltine race pre, with known genetic background were utilized in different combinations in the cross breeding programme including test crossing and backcrossing at appropriate stages by following suitable selection procedure for the ten economic traits considers at every generation, a hardy new bivoltine breed MU51 is evolved, which is characterized by plain larvae spinning white oval cocoons with shorter larval duration (20-22 days) was isolated in the selected breeding experiment.